TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI TUNANETRA TENTANG MENARCHE DI SLB Y TANJUNG MORAWA TAHUN 2018 - Sarinah Sarinah (Poltekkes Kemenkes Medan, 2020)
Menarche is the first menstruation that usually occurs in the age range of 10-16 years or in early adolescence in the middle of puberty before entering the reproductive period. Knowledge is the result of knowing and this happens after people have sensed a certain object. Sensing occurs through the human senses, namely: vision, hearing, smell, taste and touch. Attitude is a reaction or response of someone who is still closed to a stimulation or object. The manifestation of that attitude cannot be directly seen, but can only be interpreted in advance from closed behavior.This research uses descriptive quantitative method, namely to find out the description of the level of knowledge of blind young women about menarche at Y Tanjung Morawa SLB 2018. The population in this study were all the number of young women at Y Tanjung Morawa SLB aged 10-18 years. And the sample in this study is the entire population. Data collection using primary data. From the results of research on blind teenage girls at Y Tanjung Morawa SLB in 2018 the majority of knowledge is less than 60% and the minority of good knowledge (16.67%) The majority of respondents aged 10-12 years lack knowledge as much as 23.33%, sufficient knowledge 13, 33% and good knowledge as much as 10%, minorities are found at the age of 16-18 years with less knowledge as much as 10%, sufficient knowledge as much as 6.67% and good knowledge as much as 3.33%. The majority of information sources from the environment are lack of knowledge as much as 33.33%, sufficient knowledge of 10% and good knowledge as much as 6.67% of the source of information from health professionals is enough (3.33%). The majority of adolescent attitudes are negative as much as 56.67% and minority positive teen attitudes as much as 43.33%. From the results of the study it is expected that young women will increase their knowledge about menarche because it is very important to maintain personal hygiene during menarche or menstruation.